Evaluating aflatoxin gene expression in Aspergillus section Flavi - Rodrigues, Paula (2017)
The determination of aflatoxin production ability and differentiation of aflatoxigenic strains can be assessed by monitoring the expression of one or several key genes using reverse transcription polymerase chain reaction (RT-PCR). We herein describe the methods for RNA induction, extraction, and quality determination, and the RT-PCR conditions used to evaluate the ability of a given Aspergillus strain to produce aflatoxins.